Perancangan Aplikasi Pembelajaran Mathematic Game Menggunakan Metode Finite State Machine dan Construct 2 - Tiara Puspita Arin; Miftahur Rahman; Syarif Hidayatullah (Universitas Muhammadiyah Riau, 2023)
This study aims to increase interest in learning Geometry Mathematics through learning media using games or games in class VIII students of SMPN 3 Tanggul, Jember Regency. The existence of educational games is expected to be a medium for learning mathematics that is not boring and easy to understand. The system development method used in this study is the Multimedia Development Life Cycle (MDLC). To make the game interesting, the Finite State Machine method is added to make smart enemies and characters more interesting, fun and the game is made using Construct 2. Testing is done in two ways, namely testing the application system with a black box and testing the feasibility of the application by distributing questionnaires. From the results of software testing using a black box that with black box testing this application system can run well. While the questionnaire testing is based on the Likert scale categories, the results obtained from media experts and material experts got an average score of 3.92 in the good category and 4.57 in the very good category. The results of testing individual students get results between 2.6 - 4.6 in the good - very good category. While the overall test gets an average of 3.9 in the good category.